2020
DOI: 10.1101/2020.02.13.947366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human hormone seasonality

Abstract: Hormones control the major biological functions of stress response, growth, metabolism and reproduction. In animals these hormones show pronounced seasonality, with different set-points for different seasons. In humans, the seasonality of these hormones remains unclear, due to a lack of datasets large enough to discern common patterns and cover all hormones. Here, we analyze an Israeli health record on 46 million person-years, including millions of hormone blood tests. We find clear seasonal patterns: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…Our results show that although humans have the capacity to reproduce year-round, there is seasonal structuring to our reproductive physiology. Early findings of increased estradiol in the winter (35) have recently been confirmed by a large-scale study (36) that revealed a winter-spring peak in estradiol and testosterone and a summertime peak in luteinizing hormone (LH) and prolactin (36). In addition to seasonal variations in reproductive hormones, humans have seasonal cycles in hormones involved in thermoregulation, metabolism, stress adaptation and growth (36), as well as seasonal changes in the immune system (37,38).…”
Section: Discussionmentioning
confidence: 95%
“…Our results show that although humans have the capacity to reproduce year-round, there is seasonal structuring to our reproductive physiology. Early findings of increased estradiol in the winter (35) have recently been confirmed by a large-scale study (36) that revealed a winter-spring peak in estradiol and testosterone and a summertime peak in luteinizing hormone (LH) and prolactin (36). In addition to seasonal variations in reproductive hormones, humans have seasonal cycles in hormones involved in thermoregulation, metabolism, stress adaptation and growth (36), as well as seasonal changes in the immune system (37,38).…”
Section: Discussionmentioning
confidence: 95%
“…Karin et al showed that such mass changes are sufficient to explain HPA dysregulation after prolonged stress. (Tendler et al, 2020) proposed that the same model can explain seasonal entrainment of hormones and their seasonal peaks and troughs. Here, we propose that the mass changes provide a ''memory'' to the HPA axis, which can integrate over the fast timescale fluctuations of stress inputs to generate fluctuations that last on the timescale of a year.…”
Section: Discussionmentioning
confidence: 99%
“…We employ a recently developed model for the HPA axis, which incorporates the effects of the hormones on the total functional mass of hormone-secreting cells (Karin et al, 2020;Tendler et al, 2020). The concentrations of the hormones CRH, ACTH and cortisol are denoted , and .…”
Section: Hpa Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Anonymized data and the source code used to perform the analysis is available at the GitHub repository: https://github.com/alonbar110/Human-hormone-seasonality ( 60 ).…”
Section: Data Availabilitymentioning
confidence: 99%